Airway Epithelial Cell Immunity Is Delayed During Rhinovirus Infection in Asthma and COPD - Veerati, Punnam Chander; Troy, Niamh M.; Reid, Andrew T.; Li, Ngan Fung; Nichol, Kristy S.; Kaur, Parwinder; Maltby, Steven; Wark, Peter A. B.; Knight, Darryl A.; Bosco, Anthony; Grainge, Chris L.; Bartlett, Nathan W. (Frontiers in Immunology, 2020)
Respiratory viral infections, particularly those caused by rhinovirus, exacerbate chronic respiratory inflammatory diseases such as asthma and chronic obstructive pulmonary disease (COPD). Airway epithelial cells are the primary site of rhinovirus replication and responsible of initiating the host immune response to infection. Numerous studies have reported that the anti-viral innate immune response (including type I and type III interferon) in asthma is less effective or deficient leading to the conclusion that epithelial innate immunity is a key determinant of disease severity during a rhinovirus induced exacerbation. However, deficient rhinovirus-induced epithelial interferon production in asthma has not always been observed. We hypothesised that disparate in vitro airway epithelial infection models using high multiplicity of infection (MOI) and lacking genome-wide, time-course analyses have obscured the role of epithelial innate anti-viral immunity in asthma and COPD. To address this, we developed a low MOI rhinovirus model of differentiated primary epithelial cells obtained from healthy, asthma and COPD donors. Using genome-wide gene expression following infection, we demonstrated that gene expression patterns are similar across patient groups, but that the kinetics of induction are delayed in cells obtained from asthma and COPD donors. Rhinovirus-induced innate immune responses were defined by interferons (type-I, II and III), interferon response factors (IRF1, IRF3 and IRF7), TLR signalling and NF-B and STAT1 activation. Induced gene expression was evident at 24 hours and peaked at 48 hours post-infection in cells from healthy subjects. In contrast, in cells from donors with asthma or COPD induction was maximal at or beyond 72-96 hours post-infection. Thus, we propose that propensity for viral exacerbations of asthma and COPD relate to delayed (rather than deficient) expression of epithelial cell innate anti-viral immune genes which in turns leads to a delayed and ultimately more inflammatory host immune response.